Indonesia : 2011 Article IV Consultation: Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Indonesia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The Indonesian economy proved resilient during the global financial crisis, and has since continued to grow at a robust rate. Increases in both foreign and domestic investment are expected to offset lower growth contributions from net exports as import demand rises. A key risk is deterioration in growth for advanced economies. Continued exchange rate flexibility will be important in managing volatile capital flows, and the build-up in reserves. Fiscal developments are consistent with the government's firm commitment to sustainability and strong public finances.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet